Degeneracy pressure of mass dimension one fermionic fields and the dark matter halo of galaxies - Pereira, S. H. [UNESP] (2022)
In this paper, the recently proposed mass dimension one fermionic field is supposed to be responsible for the dark matter (DM) halo around galactic nuclei, through the quantum degeneracy pressure effect of the field. It will be shown that the mass-ratio relation for dwarf galaxies can be well explained for a particle DM mass of about 100-200eV. For a large galaxy, as Milky Way, the observational data for rotation curve can be well reproduced for a particle mass of about 23eV, with the addition of other substructures.